SISTEM SIMPANAN WADI'AH DHOMANAH DAN RESIKO DALAM KAJIAN JASA KEUANGAN SYARIAH - Mustofa Mustofa (LP2M Universitas Ibrahimy, 2013)
Institute of Islamic Banking in Indonesia emerged in 1992 when in sahkannya Constitution Act No 7 of 1992 the Constitution Act is beginning to accommodate Islamic banking as banking for the results, then was replaced by Law No.. 10 of 1998.Banking functions are as intermediaries (intermediary institution) between the owner of the funds and those who need funds, for which the main activity of Sharia Financial Services Unit is to collect funds from the public and the channel back in the form of financing.The problem faced is how the implementation of the principles of Shari'ah in the contract wadi'ah Economics dhomanah and risk in the Financial Services Unit Shariah